The integral visit to the family. Methodological guide for its execution - Anabel Geroy Fernández; Ana Teresa Fernández Vidal; Anais de la Caridad Núñez Herrera; Tania López Otero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: the comprehensive visit to the family contributes achieving the actions and the specific functions declared in the Program of the Family Doctor and Nurse in Cuba. It must be executed by basic health teams in each of the doctor's offices. Objective: to propose a methodological guide for the comprehensive visit to the family by the members of the basic health team. Methods: this research responds to a development project and was carried out from March to September 2018. The nominal group technique was applied with the participation of experts (postgraduate methodologists from different areas and municipalities of the province) following the established stages: list preparation, list presentation, voting and assessment and debate of the results achieved with the contribution of all the members of the group. The inclusion of individual trials was achieved until arriving to a consensus in the proposals. Results: the guide provides the steps to follow in the comprehensive visit to the family, among which stand out: characteristics, state of health, material, hygienic-sanitary and epidemiological conditions, family scheme, family functioning, etc., including a joint action doctor-family plan, to solve the problems detected. Conclusion: the methodological guide for developing the comprehensive visit to the family by the basic team members contributes to the achievement of main basic action with the required quality, fulfilling the proposed objectives in the Program of the Family Doctor and Nurse.